PEMBAGIAN KERJA SECARA GENDER PADA MASYARAKAT NELAYAN DI INDONESIA - Indrawasih, Ratna (Jurnal Masyarakat dan Budaya, 2004)
The technological changes and market economic orientation are factors affecting the change of activities of both male and female workers as well as distribution of work in the household. On the fisher societies, the technological changes have made female workers to involve from productive to pasca productive activities. That also change distribution of work on male and female workers. Firstly, both of husband and wife do together in productive and pasca productive activities, such as fishing and fish processing, and both of them also conduct a domestic activities. Due to technological changes, fishing activitities is only conducted by male (husband), while female (wife) do fish processing, marketing and also domestic activities. In other words, technology changes tend to set free a male from domestic activities (household duties).